Pendampingan Pengelolaan Bank Sampah Sukses Mandiri Kelompok Usaha Pengrajin Bahan Plastik Kampung Jambu Cimaung Kabupaten Bandung - Suwandi, Yudi Wahyudin; Marlina, Reni; Said, Lina (Empowerment, 2022)
The implementation of the waste bank is a community social engineering activity to sort waste.  Through the establishment of a waste bank, people are not only sorting out but how to be productive and innovative.  By processing waste into valuable items, people become educated and appreciate each waste according to its value and type.  Waste management is regulated in the Government Regulation of the Republic of Indonesia number 81 of 2012 concerning the Management of Household Waste and Waste Similar to Household Waste, that waste processing sites have the principle of 3R (Reduce, Reuse, Recycle).  In accordance with the government regulation, the activity initiated by the Cipinang group RT 01 RW 12, Cipinang Village, Cimaung District, Bandung Regency with 20 members is trying to establish a Waste Bank which is managed independently with the help of youth who are members of the Youth Organization.   The main problem is related to human resources and technical equipment that supports waste management. The assistance provided is related to operational technical aspects, institutional or management aspects, financing aspects and community participation aspects.